O papel da luz de diodo infravermelho em modelo experimental de asma resistente a corticoide - Brochetti, Robson Alexandre (2021)
Asthma is a heterogeneous disease generally characterized by chronic and reversible inflammation of the bronchi with inflammatory cells, smooth muscle cell hypertrophy, and bronchial airway hyperreactivity. It is defined by a history of respiratory symptoms, such as wheezing, dyspnea, retrosternal chest tightness, and coughing, which vary with time and intensity, and predominantly at night and in the morning. Corticosteroids are the mainstay of asthma treatment as they block the production of inflammatory cytokines. However, a considerable proportion of patients with asthma do not respond to corticosteroid therapy, even when administered in high doses, these patients present a profile of resistance to the anti-inflammatory actions of corticosteroids, developing a more severe type of asthma, with cellular characteristics of the neutrophilic type, than eosinophilic, which differs from allergic asthma, and this type of asthma is characterized by steroid-resistant asthma. In this sense, our objective was to evaluate the effect of photobiomodulation using infrared light emitting diodes (LEDs) on the development of corticosteroid-resistant asthma. Therefore, we used male Wistar rats and randomly divided them into 4 groups: basal group, unmanipulated control rats; ARC group: asthmatic rats; ARC+LED group: asthmatic rats treated with LED and ARC+DEXA group: asthmatic rats treated with dexamethasone. The three groups, except the basal group, were sensitized on the 1st day with grade V ovalbumin plus complete freund's adjuvant (FA) and on the 21st and 22nd day underwent inhalation challenge (nebulization) with 1% ovalbumin grade III, to create neutrophil-type corticosteroid-resistant asthma; the ARC + LED group was treated with the LED directly on the skin over the respiratory tract at a single point, in the parameters: wavelength 810 nm; power 100 mW; energy density 5 J/cm; total energy 15J; time 150s; The ARC + Dexa group was treated with the drug dexamethasone (2mg/ml) injected intraperitoneally (ip) on the 21st and 22nd days 3 hours before each inhalation challenge. Therefore, we evaluated pulmonary inflammation (total number of cells in the BAL), the determination of myeloperoxidase activity, inflammatory and anti-inflammatory drugs (cytokines), gene expression and mast cell degranulation. Our experimental model was able to induce asthma with neutrophil characteristics. Corticosteroid treatment did not reverse cell migration to the bronchoalveolar lavage, nor did it reduce the levels of leukotriene B4, interleukins 17 and 6. Treatment with FBM, on the other hand, reduced cell migration to the alveolar space, myeloperoxidase activity, degranulation of mast cells and the levels of leukotriene B4, thromboxane B2, prostaglandin E2, tumor necrosis factor alpha and interleukins 17 and 6. In addition to the increase in the level of interleukin 10, by FBM. We show promising effects of LED in the infrared range when irradiated directly into the respiratory tract as an alternative treatment for corticosteroid-resistant asthma.